Effect of Endostar combined with concurrent chemoradiotherapy in patients with locally advanced cervical cancer - Hengzhao Zhuang; Yang Jiao; Xin Li; Jingping Yu; Juying Zhou; Lili Wang (Radiation Medicine and Protection, 2023)
Objective: To explore the value of Endostar in the clinical application of locally advanced cervical cancer. Methods: A total of 107 patients with locally advanced cervical cancer who received concurrent chemoradiotherapy (CCRT) in the Department of Radiotherapy, the First Affiliated Hospital of Soochow University and Changzhou No.2 People's Hospital between January 2018 and December 2020 were enrolled in this retrospective study. There were 30 cases in the Endostar combined with CCRT (E-CCRT) group and 77 in the CCRT group. Propensity score matching (PSM) was used to reduce confounding factors. The short-term efficacy and long-term survival rate were compared between the E-CCRT group and the CCRT group. Results: After matching, the objective response rates in the E-CCRT group and CCRT group were 86.7% and 63.3%, respectively, with statistically significant difference (χ2 = 4.356, P ​= ​0.037). But there were no statistically significant differences in the disease control rates (96.7% vs. 86.7%, χ2 = 0.873, P ​= 0.350), 3-year overall survival (OS) rates (86.7% vs. 83.3%, P ​= ​0.681), and 3-year disease-free survival (DFS) rates (both 76.7% and 76.7%, P ​= ​0.869). There was no statistically significant difference in the incidence of adverse reactions between the two groups. Conclusions: E-CCRT can improve the response of locally advanced cervical cancer patients without increasing the occurrence of adverse reactions, and has the potential to become a new treatment regimen for cervical cancer.